WORKSHOP OF FORMULATION AND EVALUATION BLUSH ON PREPARATION FROM RED ROSE EXTRACT (ROSA DAMASCENE MILL) - Cucu Arum Dwi Cahya; Rahmah Tusyifa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Blush On is a cosmetic preparation that can be used to color the cheeks and aims to produce a tapered and fresher accent on the face. Roses (Rosa damscene Mill) is known to have anthocyanin content that serves as a natural dye and as a bioactive compound that can act as a free radical catching material. The purpose of this study is to make use of red roses as a natural dye on cosmetic preparations namely blush. The extract is obtained by maceration using aquadest and citric acid, blush on formulation made dye from red rose extract with a concentration of 2%, 4% with talcum, zinc oxide, kaolin and nipagin ingredients. Tests conducted include: homogeneity test, organoleptic test, pH test, oles test, irritation test, and crack test. The results of the study with a concentration of 2% and 4% produced a homogeneous blush, pH preparations ranging from 5.0 – 5.5, not cracked when dropped from a height of 8-10 inches, preparations do not irritate. The conclusion of this study shows that red rose extract (Rosa damscene Mill) can be used as a dye in blush preparations. the higher the concentration of the extract used, the darker the pigment color on the preparation.